THE USE OF MIND MAPPING TECHNIQUE IN WRITING DESCRIPTIVE TEXT - Alma Prima Nurlaila (Journal of English and Education, 2013)
This paper will discuss the result of a study on the effectiveness of mind mapping technique in teaching writing Descriptive texts to seventh-graders in a Junior High School in Bandung. This research used a mixed method between pre-experimental design particularly one group pretest-posttest design and questionnaire and interview techniques. The results indicate that there is a significant improvement in students’ writing ability, as can be seen from the results of the t-test, in that the  tobt is higher than the tcrit (7.821 2.021) at the level significance 0.05 (two-tailed). Furthermore, the results of questionnaires show that most students (86.1%) gave positive responses toward the use of mind mapping technique in writing Descriptive text. Finally, the results of interviews suggest that the students loved this technique because it successfully motivated them to write Descriptive texts in an enjoyable way,  to improve their writing Descriptive texts, to increase vocabulary and creativity, to arrange sentences and organize  ideas. It is then recommended that mind mapping technique be used in teaching writing in different text types and levels of scholing.  Keywods: Mind mapping technique, writing, descriptive texts